Smart cloud robot using raspberry Pi - Prabha, S. Sathya; Antony, A. John Paul; Meena, M. Janaki; Pandian, S. R. (2014 International Conference on Recent Trends in Information Technology, 2014)
Cloud robotics is an emerging field that is centered on the benefits of converged infrastructure and shared services of a cloud computing environment. In this paper, a system is designed with an autonomous robot to sense environmental data such as temperature, humidity, and air quality, along with GPS coordinates and store them on the cloud. The mobile robot is controlled using an Arduino microcontroller and communicates with the cloud via a Raspberry Pi. A private cloud is set up using OpenStack that provides Infrastructure as a Service. The collected data are stored in a cloud server which could be viewed through a web browser and can be used to create awareness about the environmental changes of the location under study. A proof-of-concept prototype has been developed to illustrate the effectiveness of the proposed system.